IMPLIKASI PARADIGMA BARU PENDIDIKAN AGAMA ISLAM TERHADAP KURIKULUM DAN PRAKTIK PEMBELAJARAN PAI: STUDI KASUS DI SDN 1 CARINGIN KABUPATEN SUKABUMI - Cahaya Oktafiami; Mulyawan Safwandy Nugraha (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
The new paradigm of Islamic Religious Education (IRE) emphasizes holistic student development through the integration of cognitive, affective, and psychomotor aspects, as well as the reinforcement of religious moderation values and the contextualization of Islamic teachings in daily life. This study aims to analyze the implications of the new paradigm of Islamic Religious Education for curriculum development and learning practices at SDN 1 Caringin. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews with IRE teachers and the school principal, and documentation studies of instructional materials. The findings indicate that the new IRE paradigm has implications for a more flexible curriculum design oriented toward character building and the implementation of active, reflective, and contextual learning strategies. The learning practices at SDN 1 Caringin have moved toward participatory learning through discussions, habituation of Islamic values, and the integration of religious values into school activities. However, several challenges remain, including limited supporting facilities and varying levels of teacher competence in implementing the new paradigm. This study is expected to contribute to the development of IRE curricula and learning practices that are more responsive to contemporary educational demands.